Design and development of a solar energy-based egg incubator using the quality function deployment (QFD) method with an automatic sliding rack - Silitonga, Muhammad Prasha Risfi; Muklas, Muchamad Wali; Prakoso, Muhammad Azhar; Adhi, Pribadi Mumpuni; Maladzi, Radhi (Politeknik Negeri Lhokseumawe, 2025)
This research focuses on the design and development of a solar-powered egg incubator specifically for free-range chickens, incorporating an automated sliding rack mechanism. One of the main issues encountered by poultry farmers is the inconsistency of electricity supply and the uneven distribution of heat within conventional incubators, both of which contribute to low hatch rates. To address this, the study employed the Quality Function Deployment (QFD) methodology alongside the House of Quality (HOQ) framework to systematically convert user requirements into engineering specifications. Primary data were gathered through Focus Group Discussions (FGD) with poultry practitioners, followed by experimental evaluations concerning thermal distribution performance and the reliability of the solar-powered backup system. Findings demonstrate that the integration of the automated rack and solar panel system resulted in a full (100%) hatching rate, with a stable incubation temperature maintained within the optimal range of 37 to 40°C. Additionally, the solar energy system ensured uninterrupted operation for approximately 7 hours in the event of a power outage. This technological innovation offers a sustainable, eco-friendly solution that holds the potential to significantly boost the productivity of local poultry farming.